Bioconversion of Black Soldier Fly (BSF) from Organic Waste Composting into Biodiesel Assisted by Whole Cell Microbial Lipase Biocatalyst through Direct Transesterification Process - Sari Sekar Ningrum; Aidha Zulaika; Briantama Hanif S; Dewa Ayu Dinda (Jurnal Presipitasi : Media Komunikasi dan Pengembangan Teknik Lingkungan, 2023)
Black Soldier Fly or Hermetia Illucens (BSF) is known for its potential as a biological agent that helps in the process of natural conversion of organic waste. Resulting compost and a large number of BSF colonies, potentially to be use as a non-food raw material in bioenergy production. The Method is BSF conversion experiment by direct transesterification reaction using Lab-scale bioreactor in 100ml three bottle neck flasks, the solution mixture consists of BSF powder, immobilized whole cell biocatalyst, and solvent. The Result is although in appearance the structure of the test mixture solution did not show an oily character, but based on the viscosity and density test, the test solution had density value 0.81 g/cm3 and viscosity value 1,024 mm2 /s which are above the value of the viscosity and density of methanol but still below the value of the viscosity and density of both SNI and EN14214 biodiesel standard, this could be due to insufficient separation or reaction, imperfect condition, and impurities that are still present in biodiesel products. It can be concluded that a transesterification reaction has occurred in this trial, however further analysis and more experiments are required to definitely conclude the changes in biodiesel production.